The Impact of Knowledge Transfer and Knowledge Assimilation on Project Performance - Naseem, Aliya; Abbas, Rameesha (Advances in Social Sciences Research Journal, 2022)
The purpose of this quantitative, non-experimental research was to utilize the theory of Knowledge Management proposed by Landaeta (2008) that relates the cross-project knowledge transfer methods across projects to knowledge assimilation of the receiving project, and project performance for practicing project managers in Pakistani organizations. Unique to this study was the analysis of knowledge assimilation as a mediator to knowledge transfer methods and project performance. The data was collected from 151 respondents working in different project-based organizations in Pakistan, and the data was assessed using structural equation modeling. The results revealed that knowledge transfer and knowledge assimilation have significant influence on project performance. This study also proposes contributions to the theory and implications for the managers.